(untitled) (INTEGRATION PROCEEDING, 2023)
English educational content brings new dimensions to enhancing language learning and engagement. Social media existence facilitates people with a variety and creative English educational content based on their needs. This phenomenon serves as an opportunity and challenge for EFL students to be more creative in developing teaching media on social media. This paper shares how EFL students experience developing educational content as their language course tasks. A narrative approach was employed in this study. The subject of this study is EFL students from 3 different universities. Drawing on semi-structured data, the researcher found that students face several challenges in preparing English educational content. They face difficulties in choosing the topic, creating the script and editing the content. This study also emphasizes the importance of preparing EFL students to create educational content in the future.